Erich Fromm's Socio-Existential Theory Tasks of Forming A “Healthy Society” In The Concept - ugli, Asatulloyev (Pubmedia Social Sciences and Humanities, 2025)
The tasks and prospects of forming a "healthy society" in the socio-existential concept of Erich Fromm, and the dehumanization of society under the influence of destructive social conditions in the work "Healthy Society", are analyzed. Also, the development of social neurosis, which is manifested in the phenomena of alienation and escape from freedom throughout human history, the genesis and essence of social neurosis and the possibility of effective human development towards realizing its integral nature, are studied. As a solution to such problems, Fromm proposed communitarian socialism as a theory that best meets the requirements of the essence and nature of man among the theories that are alternative to capitalism.